A CASE REPORT ABOUT RADIAL HEAD FRACTURE TYPE IV FOLLOW MASON CLASSIFICATION: PLATE PLACEMENT, REHABILITATION AFTER SURGERY (Vietnam Journal of Community Medicine, 2024)
Objective: To report a clinical case after direct trauma which caused elbow dislocation and radialhead fracture to discuss the clinical features and treatment of this case.Result: After 3 months of surgery, the patient came to the clinic again with a happier expressionbecause the movement had improved more than before, with the pronation / supination range reaching90 degrees / 0 / 80 degrees.Conclusion: Radial head fracture is a type of fracture that affects pronation, supination of the forearm,and elbow flexion. Surgical treatment and postoperative care require the surgeon to understand theclassification, indications and treatment techniques in order to restore the anatomy and function ofthe elbow joint.
Keywords: radial head fracture, Mason classificafion, plate placement.